2004
DOI: 10.1590/s0074-02762004000900019
|View full text |Cite
|
Sign up to set email alerts
|

Rural tourism as risk factor for the transmission of schistosomiasis in Minas Gerais, Brazil

Abstract: Recently, the booming rural tourism in endemic areas of the state of Minas Gerais was identified as a contributing factor in the dissemination of the infection with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
14

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 7 publications
0
15
0
14
Order By: Relevance
“…Thus, tourism has been the most profitable activity in Jaboticatubas, requiring less man-power and decreasing the former demanding work force. On the other hand, this activity enables schistosomiasis transmission to other people classes, those who attend the area for tourism purposes, characterizing a new risk modality (Enk et al 2003(Enk et al , 2004.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, tourism has been the most profitable activity in Jaboticatubas, requiring less man-power and decreasing the former demanding work force. On the other hand, this activity enables schistosomiasis transmission to other people classes, those who attend the area for tourism purposes, characterizing a new risk modality (Enk et al 2003(Enk et al , 2004.…”
Section: Discussionmentioning
confidence: 99%
“…However, in order to enjoy the environments and attract and accommodate visitors, natural landscapes have been modified, harming environmentally fragile areas 4 . These modifications, imposed on natural spaces and caused by the real estate speculation from tourism's dynamics, expose both the local population and visitors to the risk of acquiring diseases, including schistosomiasis mansoni 5,6,7,8,9,10 .…”
mentioning
confidence: 99%
“…However, it is important to highlight that the present study was conducted over four years, which means that seasonal cycles, such as temperature and rainfall, for example, may have affected the abundance of mollusk populations 28,29 . This study revealed several water collections colonized by mollusks of the Biomphalaria genus, including streams, dams and waterfalls, which could serve for sporting practices or for the construction of pools, providing further sources of infection by schistosomiasis among tourists 4,30 . The Estrada Real Project is based on the exploration of the touristic potential of the region, with the implementation of regional ecotourism and the preservation of the natural patrimony 17 .…”
Section: Discussionmentioning
confidence: 99%